Topology and Dynamics of Terrorism (Global Journal of Science Frontier Research, 2018)
Terrorism is a social as well as an historical problem which has attracted great concerns in recent times. This paper discusses the mathematical perspective of terrorism and possible recommendations on nipping the problem in the bud.
Keywords: connectedness; cluster point; neighbourhood; networks; terrorism